1992
DOI: 10.1111/j.1432-1033.1992.tb17332.x
|View full text |Cite
|
Sign up to set email alerts
|

Purificication and properties of Aspergillus nigerβ‐glucosidase

Abstract: j-Glucosidase was purified from a crude cellulase preparation from Aspergillus niger by affinity chromatography on a methacrylamide-N-methylene-his-methacrylamide copolymer bearing cellobiamine. The purified enzyme was a dimer with an isoelectric point of 4.0. The molecular mass of the enzyme was estimated to be 240 kDa by gel-permeation chromatography. The enzyme hydrolyzed specificically P-glucosidic bonds and catalyzed transglucosylation of the p-glucosyl group of cellobiose to yield 4-0-j-gentiobiosylgluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 23 publications
3
54
0
3
Order By: Relevance
“…T. reesei produces ␤-glucosidases at low levels compared to other fungi such as Aspergillus species (560). Furthermore, the ␤-glucosidases of T. reesei are subject to product (glucose) inhibition (102,217,417) whereas those of Aspergillus species are more glucose tolerant (138,231,724,768). The levels of T. reesei ␤-glucosidase are presumably sufficient for growth on cellulose, but not sufficient for extensive in vitro saccharification of cellulose.…”
Section: Cellulase Enzyme Systemsmentioning
confidence: 99%
“…T. reesei produces ␤-glucosidases at low levels compared to other fungi such as Aspergillus species (560). Furthermore, the ␤-glucosidases of T. reesei are subject to product (glucose) inhibition (102,217,417) whereas those of Aspergillus species are more glucose tolerant (138,231,724,768). The levels of T. reesei ␤-glucosidase are presumably sufficient for growth on cellulose, but not sufficient for extensive in vitro saccharification of cellulose.…”
Section: Cellulase Enzyme Systemsmentioning
confidence: 99%
“…In A. nidulans, an endoglucanase was identified that was developmentally regulated and that was produced only during cleisthothecial development (25). For several ␤-glucosidases, transglycosylation activity has been observed using cellobiose (33,396), cellotriose, methyl-␤-glucoside, and ethyl-␤-glucoside (407) as substrates.…”
Section: Degradation Of Cellulose and The Xyloglucan Backbonementioning
confidence: 99%
“…For this reactivity, glucosidase has been utilized for synthesis of glucosides linked with various bonds. 6,7) However it is expected that a new catalyst showing higher acceptor and linkage specificities to form favorite oligosaccharides more abundantly will be found.…”
mentioning
confidence: 99%